Extraction of oxalic acid from porang tuber by mechanical separation method - Satriadi, Hantoro; Widayat, Widayat; Sianturi, Aurelia Genesya; Alfareza, Muhammad Ircham (BIORE Scientia Publisher, 2024)
Porang tuber is a source of food that has many benefits. It also has the disadvantage of increasing the risk of health problems because of its high oxalate content. One of the methods for capturing oxalic acid from porang tuber flour is the Mechanical Separation method. Porang flour was added to ethanol-water solvent with a ratio of the solvent mixture-porang flour and an ethanol-water composition according to the variable. The mixing of porang flour and the solvent mixture were heated and added with HCl. The filtrate obtained was taken and diluted. The diluted filtrate was taken and titrated using KMnO4. This study aims to examine the effect of material size (between 60 - 80 mesh, between 80 - 100 mesh, and >100 mesh), the composition of the solvent mixture (60:40 v/v, 78:22 v/v, 96:4 v/ v), and the ratio of solvent with porang tuber flour (10:1, 15:1, 20:1) to oxalic acid yield in porang tuber flour. The results showed that the optimum conditions obtained from this RSM method are flour size of 100 mesh, composition of ethanol: water = 96:4, and the ratio of solvent to flour 20:1. Oxalic acid yield obtained in this variable is 30.2469%.